Changes in the tree and shrub layer of Wytham Woods (Southern England) 1974-2012: local and national trends compared - Kirby, K; Bazely, D; Goldberg, E; Hall, J; Isted, R; Perry, S; Thomas, R (Oxford University Press, 2014)
Changes in the woody composition of Wytham Woods since 1974 are described, related to national trends in broadleaved woodland, and used to suggest the impact of future changes such as from ash dieback disease (Chalara fraxinea). Data on the tree and shrub layer from 164 permanent 10×10 m plots distributed in a grid across the Woods are presented from 1974, 1991, 1999 and 2012, on species occurrence, regeneration, contribution to the canopy and basal area. Variations in the current and past composition and structure of the Woods are related to past forestrymanagement and natural succession/disturbance processes. These largelymirror changes shown by other surveys at a national level. Fraxinus excelsior has been increasing in prominence across the Woods since 1974, but its future is uncertain because of disease. The species most likely to increase if there is a severe decline in F. excelsior at Wytham appear to be Acer pseudoplatanus, Corylus avellana and Quercus robur. There are benefits from linking long-term studies at one site to wider less detailed surveys in order to explore the general applicability of the results.